Thermodynamic Parameters of a Solid Biofuel from Orange Peel - Morais, Leandro C. de [UNESP]; Santos, Carolina M. [UNESP]; Rosa, Andre H. [UNESP]; Pierucci, S.; Klemes, J. J. (Aidic Servizi Srl, 2015)
The global energy scenario is a widely discussed topic in these days, with growing concern about the future supplies. Thus, much attention has been given to the utilization of biomass as an energy resource. In this way, the orange peel becomes a material of great interest, especially to Brazil, which has around 9.5 million tons of this waste per year. The current research focuses and aims potential use of dried orange peels as solid biofuel. Thermal analysis of the dried peel showed three events of mass loss, and that the thermal stability of the material increases with an increase the pyrolysis temperature. The activation energy was calculated by using Osawa-Flynn-Wall method for the global process observed during the heating from the 25 degrees C up to 600 degrees C. The tests carried out indicated the potential use of waste orange peel as a solid biofuel material.